Integrating Academic Integrity into Future Professions - Spencer, Mary (Canadian Perspectives on Academic Integrity, 2021)
In this presentation you will see an example of how to introduce and reinforce academic integrity to students through integrating it into the expectations for their future profession. This presentation will focus on engineering, but the strategy can be applied more broadly. This integration allows students to understand the value and importance of academic integrity and integrity in general in their future.